Malignant osteopetrosis obscured by maternal vitamin D deficiency in a neonate - Popp, Doris; Zieger, B.; Nützenadel, Walter; Schaefer, Franz; Schmitt-Gräff, A. (European journal of pediatrics, 2000)
A neonate presented with clinical, biochemical, endocrine and radiographic features consistent with vitamin D deficiency rickets of maternal origin. Persistent hypocalcemia and subsequent development of pancytopenia, hemolysis and hepatosplenomegaly prompted further studies that led to the diagnosis of infantile osteopetrosis.